Response after Surgical Resection of Metastatic Pheochromocytoma and Paraganglioma: Can Postoperative Biochemical Remission Be Predicted? - Ellis, Ryan J (2013)
BACKGROUND: Aggressive surgical resection with intent to cure and surgical debulking procedures are commonly recommended in patients with metastatic pheochromocytoma and paraganglioma. To date there are no data on operative outcomes of patients after surgical resection of metastatic pheochromocytoma and paraganglioma to determine if such an approach is appropriate and what factors may be associated with a favorable outcome. STUDY DESIGN: Retrospective analysis of 30 patients with metastatic pheochromocytoma/paraganglioma who underwent surgical treatment. Clinical characteristics and genetic factors were analyzed as predictors of biochemical response to surgery. RESULTS: Thirty patients underwent a total of 42 operations with a median follow-up time of 24 months (range, 1 to 114). Complete disease resection (R0/R1) was achieved in 18 (42.9%) cases, while 24 cases (57.1%) were debulking (R2) procedures without intent to cure. Complete biochemical remission was achieved in 10 (23.8%) cases and partial biochemical response was achieved in 23 (54.8%) cases. Patients with disease confined to the abdomen were more likely to achieve and maintain a biochemical response postoperatively than those with extra-abdominal disease (P = 0.0003). Debulking operations were significantly less likely to achieve or maintain biochemical palliation, with only 1 patient maintaining a biochemical response 12 months postoperatively (P < 0.0001). Patients were less likely to obtain pharmacologic independence following debulking (P = 0.0003), with only 2 (8.3%) not requiring pharmacotherapy six months after the intervention. Factors not associated with biochemical response to surgery include gender, family history, SDHB mutation status, systemic therapy, and preoperative biochemical profile. CONCLUSIONS: Depending on the extent of disease, patients with metastatic pheochromocytoma/paraganglioma can benefit from aggressive operative intervention and resection with intent to cure. Debulking procedures are unlikely to achieve clinically significant biochemical response, with any biochemical response achieved being very short-lived.